Improving Students’ English Pronunciation by Using Bruno Mars’ Song Videos with Moving Lyrics (A Classroom Action Research at Second Graders of Language Program of MAN Kendal, in the Academic Year 2015/2016). (Lingua, 2020)
The purpose of this research was to prove the use of song videos with moving lyrics in improving students’ English pronunciation. Language program students were chosen as the subjects of this study by using a purposive sampling technique.This study used action research design with two cycles in the investigation. In each cycle, the students got a pre-test, a treatment, and a post-test. However, the students were given Initial Pre-Test first before the first cycle and Final Pos-Test after the second cycle. In recording the students’ attitudes, the writer used an observation checklist in each treatment. Besides, in the end of the research, the students were asked to fill a questionnaire to record their opinions relating to the medium.By looking at the data analysis, we can see that there is an improvement. The improvement is proven by comparing Initial Pre-Test (62.20) and Final Post-Test (95.72). On average, the students improve their scores by 33.40 points. Moreover, the results of two observation checklists show that C-2 OC is better than C-1 OC. It means that the students’ motivation increase after they get treatment. Those results are in line with the students’ opinions in the questionnaire in which 90% of them like the medium and agree that it can help them to improve English pronunciation.Based on the results above, it can be concluded that song video with moving lyric is able to improve the students’ English pronunciation. Furthermore, this medium effectively improves their interest, enjoyment, and involvement during learning activities. As a result, the medium is recommended for the students to learn English pronunciation independently because it can be used out of the classroom.